LITERATURE REVIEW OF MARKETING STRATEGY OF PRODUCT QUALITY, BRAND IMAGE AND E-WOM ON PURCHASING DECISIONS FOR MAKEUP PRODUCTS BY LIZZIE PARRA (BLP) AT SUMMARECON MALL BEKASI - Nayla Nur Fadilah (Draf Solusi Indonesia, 2023)
This research is a literature review that focuses onexamining strategy of product quality, brand imageand e-wom on purchasing decisions. This researchwill involve 96 respondents using a purposive sidemethod with analysis using a quantitative approach.This research will focus on products from theMAKEUP PRODUCTS BY LIZZIE PARRA (BLP) brand.Apart from that, this research will take place in thecity of Bekasi as a research object